PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR PADA KELOMPOK TANI DI KABUPATEN PROBOLINGGO - Tini Surtiningsih; Fatimah Fatimah; Ni’matuzahroh Ni’matuzahroh; Agus Supriyanto; Tri Nurhariyati (Jurnal Layanan Masyarakat (Journal of Public Services), 2018)
This community service aims to apply the method of making and liquid organic fertilizer and improving the skills of farmers in making liquid organic fertilizer. In addition to reducing the dependence of farmer groups on inorganic fertilizers and utilizing the results of sugarcane waste, namely molasses and microbes as a formula in the manufacture of liquid organic fertilizer. The method that was carried out was to increase insight into liquid organic fertilizer, and how to make it. The results of the socialization of liquid organic fertilizers showed that the insights of farmer groups increased by an average of 77% through the pretest and post test values during socialization. Based on the evaluation shows that the farmer group has been able to make liquid organic fertilizer independently. The socialization of making liquid organic fertilizer provides additional insight for farmer groups on the use of liquid organic fertilizer for agriculture.AbstrakPengabdian kepada masyarakat ini bertujuan untuk menerapkan cara pembuatan dan pupuk organik cair dan meningkatkan keterampilan petani dalam membuat pupuk organik cair. Selain itu untuk mengurangi ketergantungan kelompok tani terhadap pupuk anorganik dan memanfaatkan hasil limbah tebu yaitu molase dan mikroba sebagai formula dalam pembuatan pupuk organik cair. Metode yang dilakukan adalah peningkatan wawasan mengenai pupuk organik cair, dan cara pembuatannya. Hasil sosialisasi pupuk organik cairmenunjukkan bahwa wawasan kelompok tani meningkat rata-rata sebesar 77% melalui nilai pretest dan post test saat sosialisasi. Berdasarkan evaluasi menunjukkan bahwa kelompok tani telah mampu membuat pupuk organik cair secara mandiri. Sosialisasi pembuatan pupuk organik cair memberikan tambahan wawasan bagi kelompok tani terhadap pemanfaatan pupuk organik cair bagi pertanian.